MiR-199a-5p Plays a Pivotal Role on Wound Healing via Suppressing VEGFA and ROCK1 in Diabetic Ulcer Foot. (7th April 2022) - Wang, Hongshu; Wang, Xianyi; Liu, Xiaomin; Zhou, Jinbao; Yang, Qianqian; Chai, Binshu; Chai, Yimin; Ma, Zhongliang; Lu, Shengdi
Abstract : Diabetes mellitus (DM) is a growing health problem. As a common complication of DM, diabetic foot ulcer (DFU) results in delayed wound healing and is a leading cause of nontraumatic amputation. miR-199a-5p, a short noncoding RNA, had abnormal expression in DFU wound tissues. The expression of miR-199a-5p was significantly increased in DFU wound tissues, skin tissues of diabetic rats, and high glucose-induced cells. Vascular endothelial growth factor A (VEGFA) and Rho-associated kinase 1 (ROCK1) are directly targets of miR-199a-5p. Inhibiting the expression of miR-199a-5p alleviated the inhibition of VEGFA and ROCK1, thereby rescued impaired proliferation and migration of HG-induced cells, and restored the normal function of the cells to some extent. In diabetic rats, inhibition of miR-199a-5p significantly increased the expression of VEGFA and ROCK1, significantly promoted wound healing, and rescued impaired wound healing. miR-199a-5p and its targets showed therapeutic effect on diabetic wounds.